2011
DOI: 10.1073/pnas.1105209108
|View full text |Cite
|
Sign up to set email alerts
|

Association of selected persistent organic pollutants in the placenta with the risk of neural tube defects

Abstract: Persistent organic pollutants (POPs) have been associated with a wide range of adverse health effects. Our case-control study was performed to explore the association between placental levels of selected POPs and risks for neural tube defects (NTDs) in a Chinese population with a high prevalence of NTDs. Cases included 80 fetuses or newborns with NTDs, whereas the controls were 50 healthy, nonmalformed newborn infants. Placental concentrations of polycyclic aromatic hydrocarbons (PAHs), organochlorine pesticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(183 citation statements)
references
References 38 publications
(37 reference statements)
6
169
3
1
Order By: Relevance
“…However, in a case-control study, insignificant associations were observed between estimated maternal occupational exposure to PAHs and CHDs in offspring (Lupo et al, 2012). Ren et al (2011) investigated placental PAH levels in 80 fetuses or newborns with neural tube defects in China. The results of their study showed that the risk of a defect was 4 to 5 times greater, when the levels of PAHs were above the average of 597 ng g −1 of lipids.…”
Section: Teratogenicitymentioning
confidence: 99%
“…However, in a case-control study, insignificant associations were observed between estimated maternal occupational exposure to PAHs and CHDs in offspring (Lupo et al, 2012). Ren et al (2011) investigated placental PAH levels in 80 fetuses or newborns with neural tube defects in China. The results of their study showed that the risk of a defect was 4 to 5 times greater, when the levels of PAHs were above the average of 597 ng g −1 of lipids.…”
Section: Teratogenicitymentioning
confidence: 99%
“…pesticides and increased risk of spina bifida or anencephaly [37]. Although CVS malformations are among the most common severe birth defects, epidemiological evidence of a link with pesticide exposure is limited.…”
Section: Ijomeh 2014;27(3) 482mentioning
confidence: 99%
“…3 Notably, a recent study found a dose-response relationship between PAHs in placenta and the risk of neural tube defects. 4 Exposure to PAHs in the general population occurs mostly through inhalation of polluted air and cigarette smoke, and ingestion of food containing PAHs, with ingestion reportedly as more dominant. 5 In certain occupational settings, such as coke oven plants, dermal and inhalation exposure are the major routes.…”
Section: Introductionmentioning
confidence: 99%